La qualità della ricerca didattica - Zanniello, Giuseppe (Studi sulla Formazione/Open Journal of Education, 2021)
Two epistemological presuppositions are made explicit: the source sciences of didactics are psychology and pedagogy; Didactics uses empirical research methods. Two issues are discussed: under what conditions can the results of scientific research in the didactic field be combined? With what degree of certainty do the results of didactic research guide the actions of teachers? Arguments are made for the development of didactic knowledge and for the improvement of the social perception of didactic research in Italy. Deontological considerations for Didactics researchers are commented. Self-critical vigilance is recommended to teaching researchers.